The carbon sequestration potential of 'analog' forestry in Ecuador: an alternative strategy for reforestation of degraded pastures. (24th June 2020) - Veintimilla, Raúl Armando Ramos; MacFarlane, David; Cooper, Lauren
Abstract: 'Analog' forestry is a novel silvicultural approach for reforestation of degraded land that seeks to establish trees that are analogous in structure and ecological function to the original climax or subclimax vegetation of the region where they are planted. Analog forestry aims to strengthen rural communities, both socially and economically, with tree plantings of high biodiversity, which provide commercial products and resiliency, while avoiding agrochemicals and fossil fuels. The latter links this strategy to climate change mitigation and adaptation strategies, but there has been little analysis comparing the potential for above- and below-ground carbon storage in analog forests, as compared with more typical reforestation efforts via single-species plantations. We present the results of a study to estimate carbon sequestration levels, above- and below-ground, from an experimental analog forest system and a teak ( Tectona grandis L.f.) plantation system, in comparison with a degraded pasture system. The study found that the analog and teak plantation forest systems stored higher quantities of total carbon (178 and 141 t C ha −1, respectively), when compared with a degraded pasture system (124 t C ha −1 ). However, the teak plantation had decreased soil carbon stocks, relative to the degraded pasture. The analog forest had the best balance of both above- and below-ground carbon stored over the 17-year study period and provided a more diverse array of timber and non-timber forest products when compared with the teak plantation. This suggests that analog forestry could be a viable social–ecological approach to carbon storage and reforestation in the study region and other places with large areas of degraded pasture and a good understanding of the structure and function of the original vegetation.